2019
DOI: 10.2478/vjbsd-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Dupont Analysis of Farms in V4 Countries

Abstract: The paper deals with the analysis of factors that influence the change in return on equity (ROE) in farms of individual V4 countries – in Slovakia, Poland, Hungary and the Czech Republic. DuPont analysis denotes the decomposition of the ROE indicator and is classified as a basic pyramid decomposition. The pyramid system captures the relationship between indicators, where one synthetic indicator (ROE) is broken down into analytical indicators through linkages. In the case of a multiplicative link between indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…https://doi.org/10.17221/235/2021-AGRICECON Asset rotation as the proxy for efficiency also showed the importance of using assets efficiently in the first year. The positive effect of asset turnover on profitability was not surprising because, according to the DuPont analysis, ROA can be calculated as profit margin multiplied by asset turnover (Ladvenicová et al 2019). Considering that the market competition in the agri-food sector is strong (Grau and Reig 2021), new firms may reduce the profit margin of their products to promote sales.…”
Section: Resultsmentioning
confidence: 99%
“…https://doi.org/10.17221/235/2021-AGRICECON Asset rotation as the proxy for efficiency also showed the importance of using assets efficiently in the first year. The positive effect of asset turnover on profitability was not surprising because, according to the DuPont analysis, ROA can be calculated as profit margin multiplied by asset turnover (Ladvenicová et al 2019). Considering that the market competition in the agri-food sector is strong (Grau and Reig 2021), new firms may reduce the profit margin of their products to promote sales.…”
Section: Resultsmentioning
confidence: 99%
“…Fenyves et al [18], taking a different perspective, concluded that "the capital structure seemed to be strongly influenced by the farm structure and the relative company size". Subsequently, Ladvenicová et al [19] and Koszorús-Tarnóczi [20] focused their research on profitability indicators. The former found that return on assets and return on sales (ROA and ROS) have a pronounced effect on the fall in return on equity (ROE), while the latter found that ROA and ROE, as well as debt stock ratios, impacted the evolution of the market capitalization/equity ratio (as dependent variable) in regression analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The equity to total assets ratio (Equation ( 4)) was used to examine the capital structure. The ROA and ROS indicators were applied similarly to previous works, such as Ladvenicová et al [19], Koszorús-Tarnóczi [20], Hamad-Tarnóczi [48], and Vavrina-Lacina [49], while the equity to total asset ratio was used in line with studies by Pille-Paradi [50] and Glushchenko et al [51].…”
Section: Analysis Of Financial Performancementioning
confidence: 99%